2011
DOI: 10.1038/sc.2011.14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a newly developed catheter (SpeediCath Compact Male) in men with spinal cord injury: residual urine and user evaluation

Abstract: Objective: To evaluate the performance of a new 30-cm-long, telescoping male intermittent catheter (SpeediCath Compact Male; Coloplast A/S, Humlebaek, Denmark) in urinary bladder emptying, safety and subject acceptance vs a standard-length male intermittent catheter (SpeediCath). Materials and methods: In a prospective, randomized, multicenter, crossover non-inferiority study, 37 male intermittent catheter users self-catheterized three times with the test catheter on one test day and three times with the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
1
16
0
1
Order By: Relevance
“…Mean residual urine volumes reported by other authors range between 9 and 40 ml. [4][5][6] Notable is the wide variation in measured volumes, between 0 and 250 ml, in the present study. Nevertheless, relevant residual urine volumes 450 and 4100 ml were only observed after 6% (n ¼ 7) and 3% (n ¼ 4), respectively, of all catheterizations (n ¼ 120).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Mean residual urine volumes reported by other authors range between 9 and 40 ml. [4][5][6] Notable is the wide variation in measured volumes, between 0 and 250 ml, in the present study. Nevertheless, relevant residual urine volumes 450 and 4100 ml were only observed after 6% (n ¼ 7) and 3% (n ¼ 4), respectively, of all catheterizations (n ¼ 120).…”
Section: Discussionmentioning
confidence: 70%
“…19 There was no difference in the efficiency of evacuating urine from the bladder between the various catheter types used in the present study. In two other studies, residual urine volumes after IC using short-or standard-length catheters in male 6 and female 5 SCI individuals have been investigated. There was no significant difference in residual urine volumes between the short-and standard-length catheters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Domurath et al, 4 reported on a trial with the use of a 30-cm telescoping catheter which was compared with a 40-cm length standard catheter. That study reported a non-statistically significant trend toward patient preference for the shorter length catheter with no significant difference in post void residual when comparing groups by ultrasound measurement after catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…1 Bladder evacuation by IC in men with NLUTD is a safe and efficient method with minimal residual urine volumes. 2,3 The most common complication in patients using IC is lower urinary tract infection. 4 Second, occult urethral trauma as a result of repeated catheter introduction occurs regularly, especially in men, but most commonly does not have lasting consequences.…”
Section: Introductionmentioning
confidence: 99%